2020
DOI: 10.1016/j.tifs.2020.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Microbial inactivation by ohmic heating: Literature review and influence of different process variables

Abstract: Background: The elimination of microbial cells is one of the most critical steps in food processing. Conventional heating is the application of diffusive and convective heat mechanisms and is traditionally applied to assure food safety. However, such process is also harmful to others thermosensitive compounds, compromising desirable sensorial characteristics. The large temperature gradients caused by conventional heating result in lower thermal efficiency, overheated zones and high processing times. To overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 71 publications
1
18
1
Order By: Relevance
“…[14] also demonstrated that the effect of temperature in combination with the effects of pH and voltage gradient can considerably enhance the effectiveness of ohmic heating on E. coli O157:H7 inactivation. According to Figure 2, by increasing the temperature, the main effect of pH on Byssochlamys fulva inactivation is significant [15]. also reported that at lower pH values, the effectiveness of orange juice pasteurization during both conventional and ohmic heating was more signified.…”
Section: Inactivation Results Of Byssochlamys Fulvamentioning
confidence: 89%
“…[14] also demonstrated that the effect of temperature in combination with the effects of pH and voltage gradient can considerably enhance the effectiveness of ohmic heating on E. coli O157:H7 inactivation. According to Figure 2, by increasing the temperature, the main effect of pH on Byssochlamys fulva inactivation is significant [15]. also reported that at lower pH values, the effectiveness of orange juice pasteurization during both conventional and ohmic heating was more signified.…”
Section: Inactivation Results Of Byssochlamys Fulvamentioning
confidence: 89%
“…Previous invention use ohmic heating in the making of Frankfurt-type sandwiches by passing an electric current for a certain period of time. However, this method disappeared due to the lack of resources and technology [1]. In the last two decades, materials and designs for Ohmic heating have been improved.…”
Section: Historymentioning
confidence: 99%
“…Ohmic heating is a development of conventional heating. Conventional heating requires more time in which protein denaturation occurs and destroys nutrients in food [1]. In ohmic heating, the heat spreads evenly and quickly throughout the product due to the increasing of permeability cell wall, which this phenomenon will speed up the heating process with minimal damage to nutrition [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ohmic heating depends upon the conductivity of the sample and electric field strength; it is an inner heating process. According to Joule’s effect, the liquid medium to be processed acts as an electrical resistance (or the load) in the circuit; when the current passes through the interior of the sample, the electrical energy is thus converted into thermal energy [ 14 ]. However, it involves direct contact between the medium and active electrodes.…”
Section: Introductionmentioning
confidence: 99%